Inclusive learning in higher education: anthropology and critical consciousness lens - Supriyadi, Supriyadi; Haenilah, Een Yayah; Sinaga, Risma M.; Maulina, Dina; Yolida, Berti; Irwandani, Irwandani (Intelektual Pustaka Media Utama, 2024)
Higher education institutions have come under fire for their perceived restrictive tactics and lack of diversity among students and faculty. This article dives into the possible synergy between anthropology and critical consciousness, drawing inspiration from Paulo Freire's seminal contributions. The major goal is to create a revolutionary transition in higher education toward a more inclusive educational paradigm. Furthermore, this study investigates the influence of political landscapes on educational curriculum, emphasizing the need for a revolutionary pedagogical framework that fosters critical consciousness in both students and instructors. The prospect of developing a more equitable and inclusive learning environment within higher education becomes reachable via the harmonic integration of different pedagogical techniques, one that is sensitive to the diverse requirements of all learners. This attempt, however, is not without difficulties, such as opposition to change and the political terrain's intricacies. Professional development opportunities and coordinated efforts between educators, administrators, and policymakers are required for successful implementation. To summarize, the priority of social responsibility in higher education is evident, and adopting transformational pedagogy is critical for tackling the multiple issues inherent in the twenty-first century.